Acceptorless Dehydrogenation of Nitrogen Heterocycles with a Versatile Iridium Catalyst1. Issue 27 (17th May 2013) - Wu, Jianjun; Talwar, Dinesh; Johnston, Steven; Yan, Ming; Xiao, Jianliang
<x xml:space="preserve">Abstract</x> Gas up: A cyclometalated iridium complex is found to catalyze the dehydrogenation of various benzofused N‐heterocycles, thus releasing H2. Driven by as low as 0.1 mol % catalyst, the reaction affords quinolines, indoles, quinoxalines, isoquinolines, and β‐carbolines in high yields.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>